Effectiveness Of Inspecsi Applications On The Quality Of Nursing Care Documentation - Ernawati Ernawati; Netha Damayantie; Mursidah Dewi; Muliyadi Muliyadi (Universitas Pahlawan Tuanku Tambusai, 2025)
Nursing services require an effective and efficient nursing management system so that nursing resources can be directed toward producing quality nursing care, one of which is through nursing supervision. Supervision is a personal observation of functions or activities in the nursing care process, which involves delegation or activities to maintain accountability and evaluate nursing care appropriately. The purpose of this research is to develop a clinical supervision application to improve the quality of nursing supervision implementation in hospitals in the city of Jambi. The clinical supervision research is designed with an application as a guide and information for ward heads, team leaders, and implementing nurses in conducting clinical supervision, thereby improving the quality of nursing supervision implementation in hospitals. The research design uses a mixed-method approach, with qualitative research on conceptual development and quantitative research used in the product development and testing phases. The research procedure follows the steps of analyze-design & development-formative evaluation using the Dick and Carey model. The research was conducted in three hospitals in Jambi City, namely Abdul Manap Hospital, Bratanata Hospital, and Bhayangkara Jambi Hospital from April to August 2023, with research subjects being all ward heads, totaling 16 people, and team leaders, totaling 24 people. There is a difference in user knowledge about nursing supervision before and after the development of an Android-based clinical nursing supervision education application with a p-value of 0.000 < 0.005. The model for developing a clinical nursing supervision application uses the instructional design approach of Dick and Carey, a systematic instructional design model for developing effective and efficient instructional programs. The clinical nursing supervision education application can be applied in hospitals by ward heads in carrying out supervision in inpatient rooms.